Studies on captive rearing of spotted grunter, pommadasys commersonnii (Pisces : Haemulidae) under ambient conditions - Bacela, Ntobeko (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1999)
The effects of stocking density, size grading, feeding frequency and ambient temperature on the growth performance and size variation of spotted grunter, Pomadasys commersonnii were investigated. The time that would be required to rear the species to market size was modelled. An area where maximum growth rate could be achieved under ambient temperature conditions, and therefore the location of a commercial farm within the distribution range of spotted grunter along the coast of South Africa, was predicted. The growth performance of spotted grunter was not significantly affected by stocking density. Growth performance seemed to improve with increasing stocking density. Competitive behaviour was absent among fish in the various stocking densities. Growth in terms of fork length and body weight was not significantly different between stocking densities. The highest specific growth rate, best food consumption, food conversion ratio and protein efficiency ratio of the fish were recorded at a density of 6.4 kg/m³, whereas the best condition factor was recorded at a density of 3.8 kg/m³. The lack of significant difference in many of the growth parameters between the various stocking densities suggest that juvenile spotted grunter could be reared at densities higher than 6.4 kg/m³. Further investigations are needed to determine the optimal initial stocking density of juvenile spotted grunter under ambient temperature and photoperiod conditions. Replacing the largest fish with average sized fish did not have a significant effect on the specific growth rate and competitive behaviour based on the relationship between the coefficient of variation and average size. Feeding frequency had a sIgnificant effect on food consumption, food conversion and protein efficiency ratio, and not on size increase, specific growth rate and condition factor. Its effect on competitive behaviour could not be conclusively explained. The best food conversion ratio recorded when feeding once a day showed that although the fish consumed a limited amount of food, they utilised the food that was fed most effectively. It is suggested that the fish be fed three times a day. The survival of juvenile spotted grunter was 95.6 % when feeding three times a day compared to 90 and 90.2 % when feeding once and five times a day, respectively. Fluctuating ambient temperature had a dramatic effect on specific growth rate and food consumption of spotted grunter. Growth modelling showed that the fish could be reared to a market size of 550 g (270 mm FL) in 19 months under ambient temperature conditions (23.2°C) at Richard's Bay. The optimal predicted rearing period of 19 months is approximately seven months less than that calculated for fish in the wild, and can possibly, be reduced further by feeding a balanced diet. The overall food consumption (on a dry weight basis) in the three size classes ranged from 0.15 ± 0.16 to 0.38 ± 0.35 % body weight per day. Food conversion ratio improved with increasing fish size. This relationship was attributed to diet quality and more specifically, the protein : energy ratio. As a result, fish in the large size class had the best overall protein efficiency ratio. Maximum specific growth rates of1.5, 0.84 and 0.74 % body weight per day were recorded from the small, medium and large size classes in the peak of summer with average daily temperature ranging from 21 to 22°C. Positive slopes in the coefficient of variation against fish size in the large size class indicated the presence of competitive behaviour which was attributed to the onset of adolescence. The information from this study can be used for pilot production of spotted grunter. Further research should be undertaken to investigate captive reproduction of the species.
Keywords: Grunts (Fishes)